1 Malaysia: promoting unity among the different races - Lean, M.L. (2009)
Malaysia is a relatively young country that achieved her independence in 1957. Due to massive migration in the last two centuries, Malaysia is a multi-racial country. Thus, this article describes how two dailies have played their role in promoting racial harmony among the different races in Malaysia. The discursive construction of the different races by the dailies may act as a form of barometer indicating the level of tolerance that exist among Malaysians and also, how the dailies try to reflect the cultural diversity of the different races to each other. In-depth interviews were conducted with two members of the press (i.e. senior news editor and a senior journalist) to find out the role of their respective dailies in promoting racial harmony and ethnic integration among Malaysians.